Genetic diversity using biochemical, physiological, karyological and molecular markers of Sesamum indicum L - Mesfer ALshamrani, Salha; Safhi, Fatmah Ahmed; Alshaya, Dalal Sulaiman; Ibrahim, Amira A.; Mansour, Hassan; Abd El Moneim, Diaa (Frontiers in Genetics, 2022)
genetic diversity and the relationships among sesame cultivars were investigated using physiological and cyto/molecular analysis. To our information, no studies have yet been conducted on the genetic evaluation of sesame genotypes based on cyto/molecular analysis in Saudi Arabia. This study showed that genotype Bah-312 had the highest values from physiological and biochemical traits (plant height, harvest index, total plant dry matter, seed yield, oil content, and fatty acids content). Using 20 ISSR and 25 SCoT primers, the studied genotypes amplified 233 and 275 alleles, while the average polymorphism percentage (P %) was 65.32 % (ISSR) and 77.8% (SCoT) across all the studied genotypes, respectively. To assess the markers efficiency analysis the polymorphism information contents (PIC), Marker Index (MI), Effective Multiplex Ratio (EMR), Resolving Power (Rp) were estimated. In general, primers (ISSR 2 & SCoT 21) and (ISSR 4 & SCoT 3) revealed the highest and lowest values for P %, PIC, MI, and EMR%. Furthermore, 188 positive and negative unique bands were detected, out of which ISSR generated 84, while 104 were amplified by SCoT analysis. In this regard, genotype Bah-312 generated 41 unique amplicons, and Jiz-511 genotype 23 unique amplicons. In the same context, the population genetics parameters, number of different alleles (Na), number of effective alleles (Ne), Shannon's index (I), expected heterozygosity (He), and Unbiased Expected Heterozygosity (uHe), were calculated. ISSR marker showed the highest values for all the estimated parameters. In this regard, genotype Bah-312 exhibited the highest values (1.35,1.37, 0.31, 0.21, 0.29) & (1.31,1.35,0.30,0.20,0.27) while, genotype Ahs-670 revealed the least values (1.29,1.31,0.26,0.16,0.23) &(1.14,1.26,0.22,0.15,0.20) for ISSR and SCoT markers respectively. For cytological data, according to the highest asymmetry index (AsK%) and lowest total form percentage (TF%) values, genotype Ahs-670 was the most advanced cultivar, and genotype Bah-312 was the most primitive one. According to the degree of asymmetry of karyotype (A) and intrachromosomal asymmetry index (A1), sesame genotype Ahs-670 was the most asymmetrical, and Bah-312 was the most symmetrical genotype. This study gives some helpful information about the genetic diversity of six sesame landraces. The variation harbored by these landraces could be used in sesame breeding programs.